2022
DOI: 10.1186/s42825-022-00082-7
|View full text |Cite
|
Sign up to set email alerts
|

Tannery wastewater treatment: conventional and promising processes, an updated 20-year review

Abstract: Mismanagement of various wastes especially waste water produced by tanning processes has caused serious environmental problems and ultimately impaired human health. Constant efforts have been making to alleviate the pollution of tannery wastewater (TWW), yet terminal treatment still takes dominance. In this review, research on TWW treatment from 2000 to 2021 was summarized, and main methods such as coagulation and flocculation, adsorption, biological treatment, membrane filtration, advanced oxidation process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 188 publications
0
28
0
Order By: Relevance
“…Tertiary treatment can be carried out by membrane filtration or reverse osmosis followed by evaporation or electrodialysis. 59 In developed countries, tannery wastewater treatment is usually carried out to a higher degree to meet the discharge standards for nitrogen. Advanced integrated pond systems, 60 sequential batch reactor (SBR) technology, 61,62 and membrane bioreactor (MBR) technology 63 are among the recently developed alternatives for the removal of both organic matter and nitrogen from tannery effluent.…”
Section: Treatment Challenges and Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary treatment can be carried out by membrane filtration or reverse osmosis followed by evaporation or electrodialysis. 59 In developed countries, tannery wastewater treatment is usually carried out to a higher degree to meet the discharge standards for nitrogen. Advanced integrated pond systems, 60 sequential batch reactor (SBR) technology, 61,62 and membrane bioreactor (MBR) technology 63 are among the recently developed alternatives for the removal of both organic matter and nitrogen from tannery effluent.…”
Section: Treatment Challenges and Pollutionmentioning
confidence: 99%
“…Tertiary treatment is essential for removing refractory organic compounds and inorganic salts. Tertiary treatment can be carried out by membrane filtration or reverse osmosis followed by evaporation or electrodialysis . In developed countries, tannery wastewater treatment is usually carried out to a higher degree to meet the discharge standards for nitrogen.…”
Section: Treatment Challenges and Pollutionmentioning
confidence: 99%
“…The effluent originating from the dyeing stage (WWDS) is considered the bottleneck during the treatment of wastewater from tanning, since it contains the largest number of recalcitrant substances. In fact, many researchers have made reports directed at WWDS environmental risk and toxicity assessments confirming their negative impact when discharged without appropriate treatment into the environment [ 9 ]. Furthermore, industrial wastewater treatment is an important issue in the current context, not only to protect the environment from pollution (reducing and/or eliminating pollutants) but also to conserve water resources, reduce water stress, and promote the sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate salts were considered inert substances in the electrochemical oxidation system before, serving as mobile ions in favor of current transfer. 67 However, recent studies have found that a certain number of sulfate radicals could be obtained in sulfate-rich electrolytes. Sulfate radicals, which show excellent advantages in persistent organic pollutants' degradation, are thus exploited in wastewater treatment practices, not only because they have a higher redox potential than HO˙ ( E 0 (SO 4 ˙ − /SO 4 2− ) = 2.5–3.0 V) but also a wider range of working pH (2.0–9.0).…”
Section: Introductionmentioning
confidence: 99%